An Andragogy-Based Non-Formal Education Model for Former Migrant Workers: A Study of the Desbumi Program in Juntinyuat, Indramayu - Muhamad Rizky Syawaludin Sobari; Maulana Irfan; Risna Resnawaty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Returning Indonesian migrant workers often face difficulties in socio-economic reintegration after returning to their home regions, characterized by low public participation, limited entrepreneurial skills, and dependence on unsustainable remittances. This study aims to analyze the application of andragogy principles in the Desa Peduli Buruh Migran Program by Migrant CARE within the Gema Karya Migran Group in Juntinyuat, Indramayu, as well as its contribution to the socio-economic reintegration of former migrant workers. The research method is descriptive qualitative, with data collection through in-depth interviews, participatory observation, and document analysis involving program facilitators, group members, families of migrant workers, government, and the migrant worker protection service center. The research results indicate that the program has implemented Knowles’ six principles of andragogy, namely the need to know, self-concept, role of experience, readiness to learn, orientation to learning, and motivation. This implementation has successfully restored the social functioning of group members through increased participation in village deliberations, the development of self-confidence, and the ability to independently handle licensing procedures. However, the contribution to economic reintegration remains limited because income from micro, small, and medium-sized enterprises is sporadic and dependent on orders from corporate partners. In conclusion, the Desbumi Program is effective as a social reintegration strategy, while economic reintegration requires ongoing support, particularly in the areas of market access and digital marketing.